2019
DOI: 10.18261/issn.2535-2512-2019-04-02
|View full text |Cite
|
Sign up to set email alerts
|

Kjønn og religiøse grenser: Unge muslimer og kristnes forhandlinger av kjønn i migrantmenigheter

Abstract: Artikkelen belyser unge muslimer og kristnes forhandling av kjønn i migrantmenigheter: 1) Hvordan forhandler unge muslimer og kristne forventningene knyttet til kjønn, forbundet med religiøse klesdrakter og kjønnsdelte arbeidsoppgaver? Og 2), hva kan ungdommenes oppfatninger av religiøse koder og kjønnsdelte arbeidsoppgaver fortelle om symbolsk grensedragning mellom deres tilhørighet til en minoritetsgruppe og tilhørighet til majoritetssamfunnet? Data består av 23 kvalitative intervjuer med tenåringer og unge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Most of the informants appeared to be restrained and refrained from publishing religious content to avoid social exclusion, conflict and religious discussions. This can be related to other studies of how Muslim informants have experienced Islamophobia (Bangstad, 2014, 2015; Bruckner, 2018; Morgan & Poynting, 2016; Nyhagen & Halsaa, 2016; Synnes, 2019).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Most of the informants appeared to be restrained and refrained from publishing religious content to avoid social exclusion, conflict and religious discussions. This can be related to other studies of how Muslim informants have experienced Islamophobia (Bangstad, 2014, 2015; Bruckner, 2018; Morgan & Poynting, 2016; Nyhagen & Halsaa, 2016; Synnes, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…Several studies have suggested that young people with minority backgrounds use social media frequently, and that it represents a significant arena for learning and discussion (Kayıkcı & D’Haenens, 2017; Mainsah, 2011; Panagakos, 2003; Synnes, 2019). Youth with minority backgrounds do not differ from other youth in their use of social media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The congregations played an important role in their lives by providing a sense of belonging, support in practical matters such as finding a place to live, and a network of friends and acquaintances. Similarly, Synnes (Synnes 2012) reported that many members of the Christian congregations in Oslo were asylum seekers who found social belonging and practical help in their church. In this study, some of the families found established immigrant charismatic churches in their area of residence, while others entered the Norwegian Lutheran church.…”
Section: Social Participation and Belongingmentioning
confidence: 99%
“…Still, there are signs of negotiation and change. A vast majority of Muslims residing in western countries, and particularly that of the younger generation of Muslims, show support of progressive and even feminist interpretations of Islam (Eidhamar 2017;Samani 2016;Ishaq 2017;Synnes 2019). Hence, there are great variations on how Muslims view gender issues, that span from a spectrum of conservative and patriarchal interpretations, to variations of more progressive and feminist readings of the religion.…”
Section: What Are Controversial Issues and How Can They Work As Didac...mentioning
confidence: 99%